PENERAPAN PERKULIAHAN PENDIDIKAN LINGKUNGAN HIDUP BERBASIS PROYEK UNTUK MENINGKATKAN KREATIVITAS MAHASISWA - Yamin, Yamin; Hartiningsih, Try (Natural Science Education Research, 2023)
The function of this research was to analyze the influence model Project Based Learning on study Environmental Education about creativity for students. Method used for this research constitutes the quasi of experiment method. Population and sample for this research are the students at a university in Bangkalan as many as two classes selection to be experiment class (apply the learning model of Project Based Learning on study Environmental Education) and control class (apply the learning model of Problem Based Learning on study Environmental Education). The instrument that used for this research is the test creative thinking skill, peer assessment, and assessment questionnaire of product creativity. The result showed that the average score of creative thinking skills test is 88% (very good category) with the gain score 61.58 (average score). Achievement of process creativity indicator (peer assessment) is 85%, while the achievement indicator of product creativity is 86%. Finally, the researcher conclude that the model Project Based Learning in science can use to increase creativity for students.